1995
DOI: 10.1007/bf00190156
|View full text |Cite
|
Sign up to set email alerts
|

Is outpatient laparoscopic cholecystectomy wise?

Abstract: The authors report a prospective analysis of their experience with 506 consecutive laparoscopic cholecystectomies to examine the appropriateness of outpatient or same-day laparoscopic cholecystectomy. Thirty-eight patients experienced at least one postoperative complication. The complication was clinically evident or suspected in only 4 of these 38 patients within 8 h following surgery. Thirty-nine percent and 76% of complications were clinically detected at 24 and 48 h, respectively. Nausea and vomiting occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
44
0
3

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 33 publications
4
44
0
3
Order By: Relevance
“…[5,6] Nonetheless, post-cholecystectomy pain may be moderate or even severe for some patients during the first 24 postoperative hours, and has frequently been treated with nonsteroid anti-inflammatory drugs (NSAIDs) or opioid treatment. [7,8] Local anesthetic infiltration is often used to improve pain relief after laparoscopic cholecystectomy. [5,[9][10][11][12][13] The postoperative analgesic effect of intraperitoneal administration of local anesthesia after laparoscopic gynecologic surgery has proved to be effective and safe but there is lack of consensus regarding the dose, concentration, site, and manner of administration.…”
mentioning
confidence: 99%
“…[5,6] Nonetheless, post-cholecystectomy pain may be moderate or even severe for some patients during the first 24 postoperative hours, and has frequently been treated with nonsteroid anti-inflammatory drugs (NSAIDs) or opioid treatment. [7,8] Local anesthetic infiltration is often used to improve pain relief after laparoscopic cholecystectomy. [5,[9][10][11][12][13] The postoperative analgesic effect of intraperitoneal administration of local anesthesia after laparoscopic gynecologic surgery has proved to be effective and safe but there is lack of consensus regarding the dose, concentration, site, and manner of administration.…”
mentioning
confidence: 99%
“…Robinsons et al (10) reported their experience in a public academic institution have achieved outpatient LC in 70% of an unselected patients and they have identified ASA classification, procedural duration and surgery start time as factor associated with failure of outpatient management. Some authors have come to the conclusion that appropriate patients selection lowers failure rate and patients most likely to fulfill the criteria of outpatient LC, who have an anesthetic preoperative classification of ASA grade I or II, with no previous abdominal surgery no history of acute cholecystitis and a procedural duration of shorter than 90 min (11)(12)(13). Our univariate analysis results confirmed that patients with age less than 60 years, ASA class 2 or below, and uncomplicated gallstones and disorders were suitable for outpatient LC.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have demonstrated the usefulness of local anesthetic instillation (especially bupivacaine) before the laparoscopic incision, thus contributing to the minor component of postoperative pain, the need of lower doses of analgesia, and a more rapid recovery to daily activity versus patients not receiving it or having it administered after the surgical incision (8)(9)(10)(11). Anti-emetic prevention, the utilization of propofol as a rapid anesthetic inductor with minimal undesirable residual effects, and the association during anesthetic induction of NSAIDs (ketorolac) have all permitted a successful ambulatorization of LC (6,13,14), which is according to various series around 55-97% (12)(13)(14)(15). Table V shows series reported along the development of the outpatient approach, including case numbers and ambulatorization percentage (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…This percentage in the analyzed series is around 1-39%, mainly due to postoperative symptoms (vomiting and abdominal pain), the elective conversion to open surgery, and patient insecurity (13). Some authors have come to the conclusion that patients most likely to fulfill the criteria of outpatient LC are those who have an anesthetic preoperative classification of ASA I or II, with no previous abdominal surgery, no history of acute cholecystitis episodes, and a procedure duration shorter than 90 minutes (3,14,16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation